Proximal subtotal pancreatectomy as an alternative to total pancreatectomy for malnourished patients - Nakagawa, Yuki; Kato, Hiroyuki; Maeda, Koki; Noguchi, Daisuke; Gyoten, Kazuyuki; Hayasaki, Aoi; Iizawa, Yusuke; Fujii, Takehiro; Tanemura, Akihiro; Murata, Yasuhiro; Kuriyama, Naohisa; Kishiwada, Masashi; et al. (Surgery today (Tokyo, Japan), 2021)
Purpose To investigate whether proximal subtotal pancreatectomy (PSTP) is superior to total pancreatectomy (TP) for preserving postoperative endocrine function, and to identify the pre-operative risk factors influencing prognosis after TP and PSTP. Methods The subjects of this retrospective study were patients who underwent TP ( n = 15) or PSTP ( n = 16) between 2008 and 2018 in our hospital. First, we compared the incidence of hypoglycemia within 30 days after surgery and the total daily amount of insulin needed in the 30 days after TP vs. PSTP. Then, we compared the prognoses between the groups. Results The incidence of hypoglycemia in the 30 days after surgery was significantly lower in the PSTP group than in the TP group ( n = 0 vs. n = 5; p < 0.001). The total amount of daily insulin given was also significantly lower after PSTP than after TP: (0 units vs. 18 units, p = 0.001). Lower lymphocyte counts ( p = 0.014), lower cholinesterase ( p = 0.021), and lower prognostic nutrition index ( p = 0.021) were identified as significant risk factors for hypoglycemia in the TP group. Low cholinesterase ( p = 0.015) and a low prognostic nutrition index ( p = 0.048) were significantly associated with an unfavorable prognosis in the TP group, but not in the PSTP group. Conclusions PSTP may be a feasible alternative to TP to preserve endocrine function, especially for malnourished patients.